2016
DOI: 10.1097/igc.0000000000000721
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Genomic Analysis of Formalin Fixed Paraffin-Embedded Archived Serous Ovarian Carcinoma Comparing Long-term and Short-term Survivors

Abstract: We validated both previous genomic findings in ovarian cancer and the proposed association between increased genomic instability and better survival. These results exemplify that analysis of genomic biomarkers is feasible on archived FFPE tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The factors reported to be associated with long-term survival are: grade, stage, primary mass size tumor [24], the absence of ascites [11], normal CA125 level before platinum therapy, negative Ki-67 expression, underexpression of p53 [25], age <40 years [26], performance status (PS), tumor histology [27], and stage IIIC due to nodal involvement [28] which is consistent with the results herein. At the molecular level, patterns of gene expression and genomic instability distinguish short-and long-term survivors [29][30][31][32]. Some studies have demonstrated that BRCA mutation status is associated with improved long-term survival independently of primary platinum sensitivity in stage III-IV ovarian cancer, suggesting that underlying tumor biology contributes to disease outcome [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The factors reported to be associated with long-term survival are: grade, stage, primary mass size tumor [24], the absence of ascites [11], normal CA125 level before platinum therapy, negative Ki-67 expression, underexpression of p53 [25], age <40 years [26], performance status (PS), tumor histology [27], and stage IIIC due to nodal involvement [28] which is consistent with the results herein. At the molecular level, patterns of gene expression and genomic instability distinguish short-and long-term survivors [29][30][31][32]. Some studies have demonstrated that BRCA mutation status is associated with improved long-term survival independently of primary platinum sensitivity in stage III-IV ovarian cancer, suggesting that underlying tumor biology contributes to disease outcome [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to clinical and pathological characteristics, genomic stability also seems to be a hallmark of long-term survival. For example, Stalberg et al assessed genomic profiles in an integrative genetic analysis of patients with serous ovarian cancer (6). Using single nucleotide polymorphism (SNP) arrays and targeted next-generation sequencing of 26 genes, they observed an increased genomic stability, a lower proportion of somatic copy number alterations and a lower average ploidy among ovarian cancer patients with long-term survival compared to those with early cancer-specific death.…”
mentioning
confidence: 99%
“…But it is also noted that there are still long-term survivors of recurrent ovarian cancer with survival time longer than five years. Clinical features at the time of primary therapy like optimal surgical cytoreduction and platinum-sensitivity [24], and genomic features like a lower proportion of somatic copy number alterations and a lower average ploidy [25] have been associated with long survival. Yet, there is still much unknown about the biomarkers associated with short/long survival in women with ovarian cancer.…”
Section: Ovarian Cancer-associated Gene Networkmentioning
confidence: 99%